MG-109 A novel 0.34 MB microduplication of 9Q34.3 in a patient with congenital cardiac defects and learning disabilities. (4th December 2015) - Saleh, Maha; Horsburgh, Shelly; Shago, Mary; Faghfoury, Hanna
Abstract :  Case report: We report a 19-year-old male with a learning disability and congenital heart defects. The patient also has mild dysmorphic facial features including facial asymmetry and mid-facial hypoplasia, high arched palate and dental crowding. Chromosomal microarray analysis demonstrated a 0.34 Mb duplication on 9q34.3, confirmed by Fluorescence in situ Hybridization (FISH). Relevance: The 9q34.3 duplication we report is the smallest duplication among the cases reported thus far and includes the genes EHMT1 and NELF. The clinical manifestations in our patient were similar to those described in other reported cases of larger 9q34 duplications, implying that our small duplication encompasses a critical region for brain, cardiac and craniofacial development. We also compare our patient with its 9q34 deletion counterpart, Kleefstra syndrome, and demonstrate the overlap between the two conditions.